Secondary infections in COVID-19 patients: A two-centre retrospective observational study - Şirin Menekşe; Seçil Deniz (Journal of Infection in Developing Countries)
Introduction: We sought to evaluate secondary infections (SIs) in patients admitted to the intensive care unit (ICU) for COVID-19 with respect to incidence, causative pathogens, and clinical outcomes.